Crescimento inicial do feijoeiro cultivado sobre resíduos de braquiária - Souza, E. F.C. [UNESP]; Fernandes, A. M. [UNESP]; Souza-Schlick, G. D.; Rosolem, C. A. [UNESP] (FapUNIFESP (SciELO), 2014)
Ruzigrass (Brachiaria ruziziensis, syn. Urochloa ruziziensis) is used as a cover crop in tropical regions because it has a high yield potential, is widely adapted and has a vigorous root system. However, it may affect early growth of the next crop due to allelopathy and competition for soil nitrate. A greenhouse experiment was conducted in glass-walled pots with soil to determine the effect of ruzigrass residues on the initial growth and mineral nutrition of common bean (Phaseolus vulgaris). Ruzigrass was grown in the pots for 50 days and chemically desiccated. Then, common bean was grown: without ruzigrass residues; with ruzigrass shoots placed on the soil surface; with ruzigrass roots left in the soil; and with ruzigrass shoots and roots left undisturbed. Root growth of common bean was decreased by ruzigrass residues, but shoot biomass was not affected when it was grown in the presence of ruzigrass shoots or roots alone. In pots where ruzigrass residues were undisturbed, common bean biomass yield was decreased. Nitrogen concentration in common bean shoot was not affected by ruzigrass shoot on the soil surface, an evidence that the observed decrease in common bean growth probably was due to allelopathic effects rather than competition for nitrogen.
Early growth of common bean cropped over ruzigrass residues
Keywords: Allelopathy; No-tillage; Phaseolus vulgaris; Urochloa ruziziensis